2018
DOI: 10.1021/acscatal.7b03095
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Cu Active Centers in Cu-SSZ-13 and Their Responses to SO2 Exposure

Abstract: The effect(s) of SO 2 on the two types of active sites on Cu-SSZ-13 NH 3 −SCR catalysts, Z2Cu and ZCuOH, were investigated. Two Cu-SSZ-13 catalysts with Si:Al ratios of 6 and 30 were synthesized, and they provide very different distributions of these two active sites. Inductively coupled plasma optical emission spectroscopy (ICP-OES), H 2 temperature-programmed reduction (H 2 -TPR), and diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) were utilized to characterize catalyst samples and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
208
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(231 citation statements)
references
References 46 publications
18
208
0
Order By: Relevance
“…An extra benefit for this treatment, is that a mildly aged Cu/SSZ-13 catalyst will be more resistant to sulfur poisoning. Notably, studies by Luo et al [16] and Epling and coworkers [23] provide strong evidence to demonstrate that [Cu(OH)] + -Z is much more vulnerable than Cu 2+ -2Z toward sulfur poisoning. CuO x formed during hydrothermal aging also causes SCR selectivity to decrease because this species does not efficiently catalyze SCR but is instead active in catalyzing the undesirable NH 3 oxidation reaction at temperatures above~300 • C. This problem may be circumvented with low Cu loaded catalysts where the dominance of Cu 2+ -2Z prevents CuOx formation during hydrothermal aging.…”
Section: Towards Rational Design Of Cu/ssz-13mentioning
confidence: 99%
See 1 more Smart Citation
“…An extra benefit for this treatment, is that a mildly aged Cu/SSZ-13 catalyst will be more resistant to sulfur poisoning. Notably, studies by Luo et al [16] and Epling and coworkers [23] provide strong evidence to demonstrate that [Cu(OH)] + -Z is much more vulnerable than Cu 2+ -2Z toward sulfur poisoning. CuO x formed during hydrothermal aging also causes SCR selectivity to decrease because this species does not efficiently catalyze SCR but is instead active in catalyzing the undesirable NH 3 oxidation reaction at temperatures above~300 • C. This problem may be circumvented with low Cu loaded catalysts where the dominance of Cu 2+ -2Z prevents CuOx formation during hydrothermal aging.…”
Section: Towards Rational Design Of Cu/ssz-13mentioning
confidence: 99%
“…Now after 3 years, new and exciting results have appeared in literature, especially with respect to the developing molecular-level understanding of the nature of the active Cu species under realistic operating (i.e., situ/operando) conditions, as well as the SCR reaction mechanisms [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. As such, it seems timely to review these new fundamental understandings.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-low sulfur diesel contains less than 10 wt ppm (Europe) or 15 wt ppm (US) sulfur, and the SO2 concentration in the exhaust gas typically reaches a few ppmv, which is nevertheless sufficient to reduce the low-temperature activity of the Cu-CHA catalysts significantly. [13][14][15][16][17][18][19][20][21][22][23][24] To be able to preserve the good lowtemperature activity, it is important to understand the impact of SO2 on the NH3-SCR activity of Cu-CHA based catalysts. We have recently shown that deactivation of Cu-CHA catalysts depends on the total SO2 exposure, which is the product of the SO2 concentration and the exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,17 During the regeneration, SO2 is released from the catalyst, but a certain fraction of the sulfur is retained in a stable form that resemble Cu sulfate. 13,14,[17][18][19]22 The observations that heating to 550 C results both in a partial regeneration of Cu-CHA catalysts and in the formation of a certain amount Cu sulfate, indicates that there are distinct Cu sites with a different reactivity towards SO2. 13,15,17,22 The most obvious possibility for distinct Cu sites in Cu-CHA catalysts is that the Cu can be associated with either one or two Al centers in the zeolite framework.…”
Section: Introductionmentioning
confidence: 99%
“…Shih et al [23] further used a theoretical method to support that Cu(OH) + was more prone to SO 2 poisoning than Cu 2+ . Yasser et al [24] studied that SO 2 only adsorbed on Cu 2+ when ammonia was present and formed ammonium sulfate as the main poisoning route on this site, while, SO 2 could react with [Cu(OH)] + to form copper bisulfate. Wei et al [25] studied the impact of hydrothermal aging on SO 2 poisoning over Cu/SSZ-13.…”
Section: Introductionmentioning
confidence: 99%